Nodular type but not vitamin D levels increases the risk of second primary cancers in melanoma patients: An observational study of 663 patients - Massa, A; Isasi-Fuster, A; Requena, C; Manrique-Silva, E; Kumar, R; Nagore, E (Actas dermo-sifiliográficas, 2024)
BACKGROUND: Vitamin D deficiency associates with the risk of developing many diseases, including cancer. At the molecular level, vitamin D appears to have an antineoplastic effect. However, the role of vitamin D deficiency in cancer pathogenesis remains unelucidated and numerous studies have resulted in discordant results. This study aimed to determine whether vitamin D deficiency during melanoma diagnosis increases the risk of developing non-cutaneous second primary cancers (SPC). MATERIALS AND METHODS: A retrospective study on 663 patients diagnosed with melanoma between 1 January 2011 and 31 October 2022. The effect of each variable on the development of a subsequent non-cutaneous cancer was performed using Kaplan-Meier curves and differences were assessed by log-rank tests. Cox proportional hazard univariate and multivariate models were used to quantify the effect of each variable in the time to develop a non-cutaneous neoplasia. RESULTS: Out of 663 patients, 34 developed a non-cutaneous SPC. There was no statistically significant association between vitamin D levels and non-cutaneous SPC development (log-rank, p=0.761). Age>60 years, stage III/IV, and nodular melanoma subtype were significantly associated with the development of a SPC. After multivariate analysis, only age>60 years (HR 3.4; HR CI 95%: 1.5-7.6) and nodular melanoma subtype (HR 2.2; HR CI 95%: 1.0-4.8) were included in the final model. CONCLUSIONS: Our results suggest that vitamin D deficiency is not associated with an increased risk of developing non-cutaneous SPC in melanoma patients. However, age over 60 years and nodular melanoma subtype increase the risk for non-cutaneous SPC development.
Keywords: Skin Neoplasms; vitamin D; melanom; Vitamin D; nedostatek vitaminu D; lidé; sekundární malignity; Retrospective Studies; Vitamin D Deficiency; Melanoma; Neoplasms, Second Primary; retrospektivní studie; nádory kůže; lidé středního věku; Middle Aged; Humans